A practical approach in clarifying legal drafting: Delphi and case study in Malaysia - Chong, Heap Yih; Oon, C. (Emerald, 2016)
Purpose - Legal drafting is one of the root causes for interpretation errors and misunderstandings in construction contracts. Moreover, most construction personnel do not have legally trained background. Therefore, the purpose of this paper is to determine the feasible use and practicality of Plain English in clarifying legal drafting in Malaysian construction contracts. Design/methodology/approach - Two research approaches were adopted, namely, Delphi research and case study. The Delphi method was to elicit local experts' knowledge and consensus view on the given examples of restructured contract provisions. Next, an actual case study was conducted to examine and substantiate the research findings by critically reviewing the latest and revised standard form of contract for its Plain English usage. Findings - The Delphi research shows that all the restructured contract provisions were agreed by the local experts; whereas the case study reveals that significant changes and the acceptance of Plain English in most of the contract provisions. Originality/value - The research renders insightful references in clarifying legal drafting in construction contracts based on the empirical evidence and the use of Plain English from the Malaysian scenario. It also contributes into the resolution of contractual differences and conflicts caused by the misunderstandings or interpretation problems.